2013 IEEE International RF and Microwave Conference (RFM) 2013
DOI: 10.1109/rfm.2013.6757261
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of LTE signal as a new illuminators of opportunity for passive radar applications

Abstract: Recently, there has been an evolution of mobile networks towards the fourth generation radio wireless communications (4G) as LTE (Long Term Evolution). In this paper, the feasibility of using LTE-based passive radar is investigated to take advantage of using LTE signal as illuminator of opportunity for moving object monitoring. An analysis of ambiguity function is done on a typical LTE waveform to assess the Doppler and range characteristics. The initial results and analysis show that LTE signal range and Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…As a first example for the purposes of this work, we consider the LTE (Long Term Evolution) waveform [20,21].…”
Section: A the Lte Signal And Modulation Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first example for the purposes of this work, we consider the LTE (Long Term Evolution) waveform [20,21].…”
Section: A the Lte Signal And Modulation Formatmentioning
confidence: 99%
“…LTE may operate across several frequency bands; 32 bands are defined by the standardization body 3GPP [22] with frequencies ranging from 729 MHz to 3.8 GHz. Operators are allocated specific spectrum bands depending on licensing and bandwidth requirements, with widths that are multiples of 5MHz for example in the UK operators are allocated bands of 5,10,15,20,25 and 35 MHz [23]. LTE uses various modulation formats depending on the type of information transmitted and the quality of the wireless channel with QPSK, 16QAM and 64QAM defined in the standard [24].…”
Section: A the Lte Signal And Modulation Formatmentioning
confidence: 99%
“…Among the characteristics, the LTE signal has a broad bandwidth differs from 1.4 MHz to 20 MHz which provides a high range resolution in comparison to other illuminators of opportunity (i.e., GSM, DVB and DAB). The variety of the LTE allocated frequency bands (800 MHz–3.5 GHz) allowing the LTE to be deployed in many countries, consequences a future broad coverage of the LTE in the worldwide [18]. Additionally, the number of commercial LTE networks is seeing a massive increase year by year.…”
Section: Introductionmentioning
confidence: 99%
“…The above mentioned LTE signal characteristics and other factors had motivated this research group to study the feasibility of LTE signals as the new illuminator of opportunity for passive radar applications for the first time as in [12], where the LTE signal was fully analysed based on the range, Doppler ambiguities and resolutions. The results showed that the LTE signal is attractive to be used for passive radar applications since it can achieve a good range and Doppler resolution of 8.6 m and 0.132 m/s, respectively.…”
Section: Introductionmentioning
confidence: 99%